Glial Modulation by N-acylethanolamides in Brain Injury and Neurodegeneration - Herrera, María I.; Kölliker-Frers, Rodolfo; Barreto, George; Blanco, Eduardo; Capani, Francisco (Frontiers in Aging Neuroscience, 2016)
Neuroinflammation involves the activation of glial cells and represents a key element in normal aging and pathophysiology of brain damage. N-acylethanolamides (NAEs), naturally occurring amides, are known for their pro-homeostatic effects. An increase of NAEs has been reported in vivo and in vitro in the aging brain and in brain injury. Treatment with NAEs may promote neuroprotection and exert anti-inflammatory actions via PPARα activation and/or by counteracting gliosis. This review aims to provide an overview of endogenous and exogenous properties of NAEs in neuroinflammation and to discuss their interaction with glial cells.